Room-temperature phosphorescence and anomalous piezochromism in molecular crystals enabled by iodine atomic orbital sharing - Tongge Xu; Chunguang Zhai; Ziyao Liu; Xiaoying Yang; Shuhe Hu; Yuchen Shang; Lei Yue; Jiajun Dong; Ran Liu; Quanjun Li; Mingguang Yao; Bingbing Liu (Nature Communications)
Abstract Controlling room-temperature phosphorescence (RTP) in organic materials through external stimuli is crucial for elucidating RTP mechanisms and engineering stimuli-responsive materials for various applications. However, compared to fluorescent materials, regulating RTP presents greater challenges due to its intricate photophysical processes, particularly in the quest for RTP materials with desirable stimulus-responsive properties. Here we show that when the interactions of iodine with neighboring molecules in 1,4-diiodotetrafluorobenzene (1,4-DITFB) crystals are tuned by pressure, exotic emission behaviors emerge. These emissions exhibit anomalous blue-shifted characteristics and enhanced intensities upon compression, accompanied by prolonged lifetimes. Notably, such piezochromic luminescence responses are impeded through a co-crystallization strategy that hinders iodine-iodine interactions. We further reveal that the observed anomalous emissions related to the unique state of iodine by providing additional orbitals shared with surrounding molecules. Our findings not only open pathways for designing tailored stimuli-responsive luminescent materials but also offer valuable insights into the underlying mechanisms governing organic RTP emitters.